A Schiff base-functionalized graphene quantum dot nanocomposite for preferable picric acid sensing. (July 2021) - Fan, Yuting; Tao, Tao; Wang, Huijun; Liu, Zeyu; Huang, Wei; Cao, Hui
Abstract: Fast and effective picric acid (PA) sensing in water and the air is urgently demanded environmental safety. Herein, a new sensor was designed and synthesized mediated by graphene quantum dots (GQDs) for explosive detection. The luminescent Schiff base-functionalized GQDs (Schiff-GQDs ) was immobilized on nanocomposite through in-situ electrospun. The quantitative experiment shows that the fluorescent quantum yield of Schiff-GQDs is 11.63%, four times higher than that of N-GQDs (2.71%) and seven times higher than that of dye 1 (1.51%). Luminescent Schiff-GQDs have a bigger quenching percentage, better selective detection of PA where the detection limit is 3.64 × 10 −5  M. More importantly, the naked-eye detection limit of the paper-based sensor has been up to 11.45 ng/cm 2 . Also, theoretical calculation, and proposed mechanism, as well as the host-guest interactions have been carried out for the visual detection of PA. This study can provide a useful example of novel membrane sensors for explosives combining with the two weak luminescent systems based on the molecular design of covalent-nanocomposited emission enhancement (CNEE). Highlights: The quantum yield of Schiff-GQDs is four times higher than that of N-GQDs. The selective detection limit of Schiff-GQDs is 3.64 × 10 −5  M for PA. Naked-eye detection limit of the paper-based sensor has been up to 11.45 ng/cm 2 . IGM analysis explains why the vdW interaction of Schiff-GQDs is stronger. The concept of CNEE is proposed for future molecular design.